Neurotropic Melanoma: The Management of Localised Disease - Jeremy Croker; Bryan Burmeister; Matthew Foote (Journal of Skin Cancer)
Neurotropic melanoma is a rare subtype of cutaneous malignant melanoma. Compared with conventional melanoma, it is more locally aggressive with an increased tendency for local recurrence but less likely for nodal or distant metastases. These tumours can be a diagnostic dilemma with a variety of morphological, histopathological, and immunophenotypical expressions. The often amelanotic, benign appearance may lead to treatment issues such as late presentation, diagnostic delay, misdiagnosis, insufficient surgical margins, and recurrence with resulting poor outcome. The neurotropic nature of the disease and prevalence in the head and neck region can result in perineural and neural invasion along named large nerves into the brain with resulting neuropathies. Wide local excision with adjuvant radiotherapy where indicated remains the current practice for treatment with chemotherapy predominately being reserved as a salvage treatment for patients with disseminated disease.